Proceedings of 3rd International Conference on Reliability, Infocom Technologies and Optimization 2014
DOI: 10.1109/icrito.2014.7014765
|View full text |Cite
|
Sign up to set email alerts
|

Improving performance of web applications using cloud resources

Abstract: Cloud computing has emerged as one of the enabling technologies that allows the business and IT world to use computer resource effectively and more efficiently. Microsoft Azure provides a Windows based environment for running applications and storing data on servers in data centers; SQL Azure provides data services in the cloud based on SQL Server; and .NET Services offer distributed infrastructure services to cloud-based and local applications. The main objective of the paper is to outline the steps involved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
(7 reference statements)
0
3
0
Order By: Relevance
“…Mangla N et al, (2014) illustrated that cloud computing has emerged as one of the enabling technologies that allows the business and IT world to use computer resource effectively and efficiently [13] Maheswari S and Upendra G (2017) developed a system where they showed that secure sharing of patient health records in Jelastic cloud provides the more benefits to the data owners and end users. In this paper [14], they propose an Attribute based encryption (ABE) algorithm for encryption and decryption of patient health records.…”
Section: Related Workmentioning
confidence: 99%
“…Mangla N et al, (2014) illustrated that cloud computing has emerged as one of the enabling technologies that allows the business and IT world to use computer resource effectively and efficiently [13] Maheswari S and Upendra G (2017) developed a system where they showed that secure sharing of patient health records in Jelastic cloud provides the more benefits to the data owners and end users. In this paper [14], they propose an Attribute based encryption (ABE) algorithm for encryption and decryption of patient health records.…”
Section: Related Workmentioning
confidence: 99%
“…Cloud storage resources are accessible through interfaces directly exposed to the customer: a crude web-based management console, and an Application Programming Interface (API) based on RE presentational State Transfer (REST) [2]. Microsoft Window Azure is a cloud platform that provides services for developers to build, deploy and manage applications [4]. Microsoft Windows azure gained popularity in providing good cloud computing services hence is used here [6].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Cloud application is an application with the capabilities of desktop application and a web application [1]. Desktop application is an application which gets executed in the desktop.…”
Section: Introduction To Cloud Technologymentioning
confidence: 99%